First Principles Study of Thermoelectric Properties of Skutterudites: Ir4Sb12 and Ca0.04Ir4Sb12 - Bhattarai, B.; Dahal, T.; Adhikari, N. P. (Journal of Nepal Physical Society, 2020)
First – principles calculations to study thermal and electrical properties of pristine and calcium filled skutterudite Ir4Sb12 has been carried out. Density of states (DOS) and band-structure calculations are based on Density Functional Theory (DFT) within Generalized Gradient Approximation (GGA). Transport properties are calculated using BoltzTrap software packages. Volume optimization is carried out on the basis of Murnaghan equation of states. The optimized lattice parameter of pristine Ir4Sb12 is found to be 9.4243 Å and that of calcium filled Ir4Sb12 is found to be 9.4949 Å. Our calculation shows that pristine Ir4Sb12 is a p-type of semiconductor with a narrow PBE-GGA band gap of 0.25 eV. After filling calcium, the band gap is reduced to zero showing the metallic behavior of filled compound. Band structure, density of states, variations of electrical and thermal conductivities with temperature and Seebeck coefficient show that calcium filled Ir4Sb12 has a metallic character. At Fermi level, the maximum value of thermoelectric figure of merit of unfilled Ir4Sb12 compound at temperature 400K is found to be 0.5. At the same temperature thermoelectric figure of merit calcium filled Ca0.04Ir4Sb12 is found to be around 0.03. The maximum value of of Ca filled Ca0.04Ir4Sb12 at 1000K is computed around 0.1.